2019
DOI: 10.1155/2019/9062537
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate Enhances Desensitization Induced by Oral Immunotherapy in Cow’s Milk Allergic Mice

Abstract: Background In previous studies, we showed that a fructo-oligosaccharide- (FOS-) supplemented diet enhanced oral immunotherapy (OIT) efficacy in a mouse model for cow's milk allergy. Fermentation of FOS by intestinal bacteria leads to production of short-chain fatty acids (SCFA) including butyrate. Aim To investigate the contribution of butyrate in the enhanced efficacy of OIT + FOS. Methods C3H/HeOuJ mice were sensitized and received OIT with or without FOS or butyrate supplementation. After treatment, whole b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Bacterial metabolites, e.g., butyrate and other short chain fatty acids (SCFA) generated upon the processing of dietary fibers, can also direct the development and function of Treg cells via the interaction with gut epithelial cells and dendritic cells and the induction of immunomodulatory mediators such as vitamin A metabolite retinoic acid (RA) [ 130 , 131 ]. As documented in animal models of food allergy, concentrations of butyrate, such as those measured in mature human milk, are sufficient to promote gut barrier integrity and IL-10 production, reduce the allergic response, and enhance the desensitizing effect of allergen immunotherapy (AIT) [ 132 , 133 ]. These findings are invoked to explain the beneficial anti-inflammatory, anti-allergic effects of Lactobacillus and Bifidobacterium probiotic mixtures and of a high-fiber diet [ 122 , 130 , 132 , 134 ].…”
Section: Immunologic Adverse Reactions To Foodmentioning
confidence: 99%
“…Bacterial metabolites, e.g., butyrate and other short chain fatty acids (SCFA) generated upon the processing of dietary fibers, can also direct the development and function of Treg cells via the interaction with gut epithelial cells and dendritic cells and the induction of immunomodulatory mediators such as vitamin A metabolite retinoic acid (RA) [ 130 , 131 ]. As documented in animal models of food allergy, concentrations of butyrate, such as those measured in mature human milk, are sufficient to promote gut barrier integrity and IL-10 production, reduce the allergic response, and enhance the desensitizing effect of allergen immunotherapy (AIT) [ 132 , 133 ]. These findings are invoked to explain the beneficial anti-inflammatory, anti-allergic effects of Lactobacillus and Bifidobacterium probiotic mixtures and of a high-fiber diet [ 122 , 130 , 132 , 134 ].…”
Section: Immunologic Adverse Reactions To Foodmentioning
confidence: 99%
“…Accordingly, a glutamate-enriched diet significantly increased colonic concentrations of these fatty acids in adult pigs (206). Butyrate and propionate both have been associated with the prevention of various allergic diseases and, consequently, high faecal levels of these fatty acids in early life have been associated with a decreased risk of developing atopy (207)(208)(209).…”
Section: Impact Of Glutamate On the Gut Microbiota Compositionmentioning
confidence: 99%
“…In vivo and clinical studies have validated the importance of SCFAs in food allergy. For example, Vonk et al demonstrated that butyrate supplementation enhances oral immunotherapy (OIT) desensitization in a murine model of cow’s milk allergy (CMA) [ 62 ]. In humans, in studies with pediatric patients with CMA, the ingestion of hydrolyzed formula containing a butyrate-producing probiotic L. rhamnosus GG (LGG) increased fecal butyrate levels and was associated with the acquisition of immune tolerance [ 63 ].…”
Section: The Microbiome and Underlying Mechanisms In Food Allergymentioning
confidence: 99%